What Color Was It? A Psychophysical Paradigm for Tracking Subjective Progress in Continuous Tasks. (January 2020) - Kosovicheva, Anna; Bex, Peter J.
When making a sequence of fixations, how does the timing of visual experience compare with the timing of fixation onsets? Previous studies have tracked shifts of attention or perceived gaze direction using self-report methods. We used a similar method, a dynamic color technique, to measure subjective timing in continuous tasks involving fixation sequences. Does the time that observers report reading a word coincide with their fixation on it, or is there an asynchrony, and does this relationship depend on the observer's task? Observers read sentences that continuously changed in hue and identified the color of a word at the time that they read it using a color palette. We compared responses with a nonreading condition, where observers reproduced their fixations, but viewed nonword stimuli. Results showed a delay between the color of stimuli at fixation onset and the reported color during perception. For nonword tasks, the delay was constant. However, in the reading task, the delay was larger for earlier compared with later words in the sentence. Our results offer a new method for measuring awareness or subjective progress within fixation sequences, which can be extended to other continuous tasks.